2017
DOI: 10.4103/ijo.ijo_939_15
|View full text |Cite
|
Sign up to set email alerts
|

Tear film and ocular surface dysfunction in diabetes mellitus in an Indian population

Abstract: Purpose:Ophthalmic complications in diabetes such as retinopathy, cataract, and infections have been extensively studied. Recently, attention has been drawn toward ocular surface changes in diabetes mellitus (DM). This study has been carried out to investigate the tear film and ocular surface abnormalities in type II DM patients.Materials and Methods:A total of 83 participants (130 eyes) were enrolled: 53 diabetics (80 eyes) and 30 healthy controls (50 eyes). Of the 53 diabetics, 24 patients (42 eyes) had some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…The study conducted by Kesarwani et al found a decreased tear secretion in diabetics with diabetic retinopathy. 9 Our study also supports a similar finding. The Schirmers strips showed decreased measurements of wetting as the severity of the stages of DR increased.…”
Section: Discussionsupporting
confidence: 91%
“…The study conducted by Kesarwani et al found a decreased tear secretion in diabetics with diabetic retinopathy. 9 Our study also supports a similar finding. The Schirmers strips showed decreased measurements of wetting as the severity of the stages of DR increased.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are close to those conducted by Zhang and Leiden (Van Leiden et al, 2002;Zhang et al, 2018). However, a correlation between tear film abnormality and DR has also been described in the literature (Nepp et al, 2000;Kesarwani et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Tear film abnormalities in patients with DM occur due to poor quantity and quality of tears, combined with a subnormal ocular surface. [ 15 16 17 18 ] In this study, Group 1 patients had a higher OSDI score and a significantly lower mean Schirmer, TBUT, and abnormal OSS value compared to controls. Patients with proliferative diabetic retinopathy had more severe symptoms of DED and higher OSS consistent with other studies.…”
Section: Discussionmentioning
confidence: 48%